One-Dimensional Experimental Investigation of Polyethylene Microplastic Transport in a Homogeneous Saturated Medium - Okutan, Hande Mahide; Sağir, Çağdaş; Fontaine, Claude; Nauleau, Benoît; Kurtulus, Bedri; Le Coustumer, Philippe; Razack, Moumtaz (Frontiers in Environmental Science, 2022)
Plastics are widely used in every part of life. Microplastics (MPs) are classified as emerging contaminants in nature. Yet, microplastic transportation parameters in groundwater are not characterized well. In this study, microplastic transport in saturated homogeneous mediums was investigated. For this purpose, one-dimensional column tests were performed using the fluorescent and microplastic tracers to figure out the hydrodynamic conditions for the microplastic transport. Large silica, small silica, sand, and coarse gravel were the tested mediums. The hydrodynamic transport parameters were calculated by inverse solution methodology using the experimental and the analytical solution results. Only the coarse gravel medium with a minimum 1 mm and maximum 20 mm (5 mm of median) pore sizes and kinematic porosity 40.2% were found to be suitable for the transport of the used polyethylene (PE) whose particle size was between 200 and 500 µm. It is not possible to transport PE particles of selected size from fine-grained media. Transportation occurred in coarse-grained media such as coarse gravel. The calculated dispersivity values for the coarse gravel were 2.58 cm and 3.02 cm by using fluorescent and PE tracers, respectively. The experiments showed that the used PE particles cannot be transported if the mean flow velocity is lower than 2.02 cm/min in the coarse gravel medium. The microplastic accumulation might be an issue for an actual aquifer rather than the transportation of it considering the actual groundwater flow velocity is generally much lower.